Drug-eluting versus plain balloon angioplasty for the treatment of failing dialysis access: Final results and cost-effectiveness analysis from a prospective randomized controlled trial (NCT01174472). Issue 3 (March 2015) - Kitrou, Panagiotis M.; Katsanos, Konstantinos; Spiliopoulos, Stavros; Karnabatidis, Dimitris; Siablis, Dimitris
Highlights: 1-Year target lesion primary patency significantly higher after PCB application compared to plain balloon angioplasty in the failing dialysis access. Significant difference in favor of PCB in cumulative primary patency of AVGs at 1 year. No significant difference in cumulative primary patency of AVFs treated with PCB at 1 year. Cost effectiveness analysis performed. Paclitaxel-coated balloon angioplasty proves to be a cost-effective option for treating dialysis access. Abstract: Objective: To report the final results and cost-effectiveness analysis of a prospective randomized controlled trial investigating drug-eluting balloon (DEB) versus plain balloon angioplasty (BA) for the treatment of failing dialysis access (NCT01174472 ). Methods: 40 patients were randomized to angioplasty with either DEB ( n = 20) or BA ( n = 20) for treatment of significant venous stenosis causing a failing dialysis access. Both arteriovenous fistulas (AVF) and synthetic arteriovenous grafts (AVG) were included. Angiographic follow up was scheduled every two months. Primary endpoints were technical success and target lesion primary patency at 1 year. Cumulative and survival analysis was performed. Incremental net benefit (INB) and incremental cost effectiveness ratio (ICER) were calculated and the cost-effectiveness acceptability curve (CEAC) was drawn. Results: Baseline variables were equally distributed between the two groups. At 1 year, cumulative target lesion primary patency was significantly higher after DEB application (35% vs. 5% after BA, p < 0.001). Overall, median primary patency was 0.64 years in case of DEB vs. 0.36 years in case of BA ( p = 0.0007; unadjusted HR = 0.27 [95%CI: 0.13–0.58]; Cox adjusted HR = 0.23 [95%CI: 0.10–0.50]). ICER was 2198 Euros (€) per primary patency year of dialysis access gained. INB was 1068€ (95%CI: 31–2105€) for a willingness-to-pay (WTP) threshold of 5000€ (corresponding acceptability probability >97%). Conclusion: DEB angioplasty may be a cost-effective option that significantly improves patency after angioplasty of venous stenoses of failing vascular dialysis access. Further large-scale randomized trials are warranted.